(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Research work has been carried out in view of establishing the possibilities of obtaining particle boards with intensified water- resistance on the bases of urea-formaldehyde resin and hydrophobic composition of hideglue-paraffin emulsion. The results of the research prove that the hydrophobic emulsion used is compatible with the urea resin and that it guarantees a high degree of hydrophobization of the particle boards /water- sorption below 25 %, thickness of swelling below 4 %/ under relatively high strength indicators /bending strength above 18 N/mm², internal bond strength above 0,45 N/mm²/. On the basis of a planned experiment the impact of the following technological factors has been established: content and concentration of the hydrophobic solution, pressing temperature and pressing time on the properties of particle boards based on hydrophobic urea-formaldehyde resin. The following values have been defined as optimal: content 2 %, concentration 30 %, pressing temperature 177,5 oC and pressing time 0,5 min/mm.